2017
DOI: 10.5194/hess-2017-683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the Glacial Lake Outburst Flood Process Chain in the Nepal Himalaya: Reassessing Imja Tsho's Hazard

Abstract: Abstract. The Himalayas of South Asia are home to many glaciers that are retreating due to climate change and causing the formation of large glacial lakes in their absence. These lakes are held in place by naturally deposited moraine dams that are potentially unstable. Specifically, an impulse wave generated by an avalanche or landslide entering the lake can destabilize 10 the moraine dam, thereby causing a catastrophic failure of the moraine and a glacial lake outburst flood (GLOF). ImjaLhotse Shar glacier is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Potential outburst flood volume Lake bathymetry map derived from sonar points interpolated within the lake boundary Use empirical area-volume relationships to estimate lake volume. Lake bathymetry fused into a DEM needed for outburst flood modeling Section "Changri Shar and Lhotse Glacier Outburst Floods" and "Langmale GLOF"; Cook and Quincey, 2015;Haritashya et al, 2018;Lala et al, 2018 Presence of permafrost Preconditioning of slopes Global Permafrost Zonation Index (PZI) Decreased slope stability at the transition from permafrost to non-permafrost zones, Spatial coincidence between lower most rock glacier distribution and the presence of permafrost Sections "Landslides"3.4, and "Open Data"; Stanley and Kirschbaum, 2017;landslides in Nepal, Petley et al, 2007;Gorkha Earthquake inventories images are also being used to generate time series of highresolution (2-8 m) Digital Elevation Models (DEMs) that can be used to quantify elevation and volume change of landforms and glaciers. Composite mosaics of these high-resolution DEMs are also fundamental for modeling landslides or outburst flood runouts and producing accurate landslide inventories.…”
Section: Glacial Lake Locationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential outburst flood volume Lake bathymetry map derived from sonar points interpolated within the lake boundary Use empirical area-volume relationships to estimate lake volume. Lake bathymetry fused into a DEM needed for outburst flood modeling Section "Changri Shar and Lhotse Glacier Outburst Floods" and "Langmale GLOF"; Cook and Quincey, 2015;Haritashya et al, 2018;Lala et al, 2018 Presence of permafrost Preconditioning of slopes Global Permafrost Zonation Index (PZI) Decreased slope stability at the transition from permafrost to non-permafrost zones, Spatial coincidence between lower most rock glacier distribution and the presence of permafrost Sections "Landslides"3.4, and "Open Data"; Stanley and Kirschbaum, 2017;landslides in Nepal, Petley et al, 2007;Gorkha Earthquake inventories images are also being used to generate time series of highresolution (2-8 m) Digital Elevation Models (DEMs) that can be used to quantify elevation and volume change of landforms and glaciers. Composite mosaics of these high-resolution DEMs are also fundamental for modeling landslides or outburst flood runouts and producing accurate landslide inventories.…”
Section: Glacial Lake Locationsmentioning
confidence: 99%
“…Given the unpredictable nature of glacier outburst floods, remote sensing has primarily been used to analyze floods following the events (e.g., Rounce et al, 2017a;Byers et al, 2018) or to conduct a first-pass hazard assessment for proglacial lakes (e.g., Worni et al, 2014;Rounce et al, 2017b). The latter typically utilize optical imagery and DEMs to identify potentially dangerous glacial lakes that require further investigation, which may include fieldwork and detailed flood modeling with a high-resolution DEM (e.g., Lala et al, 2018).…”
Section: Glacier Outburst Floodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Somos-Valenzuela et al 2016), the PRO version of which comes at a cost, but which can be used to model debris flows, and BASE-MENT (e.g. Worni et al 2012Worni et al , 2013Lala et al 2017), which is downloadable free of charge, but cannot model debris flows. A direct comparison of the outputs of each of these modelling tools is beyond the scope of this study, but it would be worthwhile undertaking such work in the future for the three lakes investigated here.…”
Section: Modelling Approachmentioning
confidence: 99%
“…Further, recent GLOF studies have attempted to model complex process chains in a multi-hazard proglacial lake context (e.g. Lala et al 2017;Mergili et al 2018), and it is suggested here that investigation of process chains for GLOFs from proglacial lakes in Bolivia would be a valuable undertaking in the future.…”
Section: Modelling Approachmentioning
confidence: 99%